THE ANALYSIS OF EMPLOYEE DISCIPLINE TOWARDS COMPETITIVENESS OF LOCAL BAKERY INDUSTRY IN MANADO : CASE STUDY OF KARTINI BAKERY AND DOLPHIN BAKERY - Noviyanti, Niluh Putu Audina (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Competitiveness becomes one of the most important aspects which is faced by every company. Each company has its own strategy in facing off the global and local competition. One of the things that affect the company’s competitiveness is the employee’s discipline. Employee’s activity at work and the implementation of the discipline to the employees have become major factors that greatly affect the company's performance. Local bakeries in Manado have a strong competitiveness these days. Through the application of work discipline to the employees, then Kartini Bakery and Dolphin Bakery are not worried about the tight competition in the market. The researcher analyzes the data based on the primary data by using the qualitative method. The primary data is used to answer the research questions and draw the conclusions from the research findings. In this research, the data will be taken from two companies which are Dolphin Donuts and Kartini Bakery through the interviews as the sample of this research. The researcher will retrieve the data by using an interview method of 8 informants which consist of 4 informants from each Bakery. The result shows that the activities of the employee’s discipline greatly affect the competitiveness of the company. If the company wants to strengthen their competitiveness then the employee's performance must be done very well by adhering to the principles of the employee’s discipline. The researcher recommends for the company how crucial it is to have a work discipline inside the company but the application of the systems is the essence to be able to compete against the competitors. Keywords: human resources management, employee discipline, work discipline, employee performance, competitiveness.